Feedback: The Foundation of Kind Leadership - Rebecca L Koltz; Melissa Odegard (Academic Chairpersons Conference Proceedings, 2020)
Brene Brown states that “Clear is kind. Unclear is unkind.” To give clear and direct feedback requires brave academic leaders who understand that feedback is critical to leadership success. This presentation will use a feedback model – Johari’s Window (Luft & Ingham, 1955), as a backdrop for understanding how to give productive feedback in higher education.
Keywords: Feedback; leadership; higher education; evaluation; communciation